PENGEMBANGAN AGROFORESTRI PADA LAHAN KRITIS DI GAMPONG MEUNASAH MON KECAMATAN MESJID RAYA KABUPATEN ACEH BESAR - Qanisyah; Hildanus; Eka Sri Wulandari (Jurnal Penelitian Hutan dan Sumber Daya Alam (PHSDA), 2022)
The practice of agroforestry has actually been practiced by rural communities and even in someplaces. The implementation of agroforestry has an important role in the socio-cultural aspectsof the local community so that traditional agricultural efforts carried out by converting forestland into agricultural land are the cause of frequent occurrence of critical land. Wise action isneeded in rehabilitating critical land so that it can increase land productivity, it can also createsustainable land use and improve the quality and quantity of agricultural products, one ofwhich is Agroforestry. The problem in this research is whether there is agroforestrydevelopment on critical land in Meunasah Mon Village, Mesjid Raya District, Aceh BesarRegency. The purpose of this study was to determine the development of agroforestry on criticalland in Meunasah Mon Village, Mesjid Raya District, Aceh Besar District. This research wasconducted on February 06 to March 04, 2021. The population in this study was all MeunasahMon Village community with a total population of 388 families or 1,366 people. While thesamples in this study were 50 respondents. The method used in this research is descriptivedetermination of the place of research and interviews (purposive sampling). Data collectiontechniques in this study are observation, interviews and questionnaires. Data processing usessimple statistical formulas and Likert scale calculations. Based on the results of the researchdata processing above, it can be concluded that from 50 respondents answered strongly agree32%, answered agree 45.6%, answered disagree 16.2% and answered disagree 6.2%. So, it canbe said that the development of agroforestry on the critical land of Gampong Meunasah Mon,Mesjid Raya District, Aceh Besar Regency is appropriate.